On the use of the Stern-layer and the charged-layer formalisms for the interpretation of dielectric and electrokinetic properties of colloidal suspensions - López García, José Juan (2009)
The classical description of colloidal suspensions is based on a series of assumptions that constitute the standard electrokinetic model: suspended particles are surrounded by a uniform surface density of fixed charge, the equilibrium ion density coincides with the Gouy-Chapman distribution, and the surface conductivity coincides with the conductivity of the diffuse double layer. Although highly versatile and relatively simple to compute, the classical model often fails to predict crucial experimental trends. Consequently, various attempts have been made to generalyze the standard electrokinetic model in order to encompass a broader set of experimental data. Numerical results show that the Stern-layer formalism increases the conductivity and dielectric response but decreases the electrophoretic mobility, while  the charged-layer approach leads to electrophoretic mobility values that can actually increase with the surface layer conductivity. Here we compare the predictions of these two surface layer models regarding the conductivity increment, the electrophoretic mobility, and the dielectric increment. We show that for high kappa*a (kappa and a being the reciprocal Debye length and the particle radius, respectively) and intermediate electrophoretic mobility values as well as cases when the measured mobility is higher than the maximum value predicted by the standard electrokinetic model, the experimental data can only be interpreted using the charged-layer model.